How and when workplace ostracism influences employee deviant behavior: A self-determination theory perspective - Luo, Jian; Li, Shuang; Gong, Lizhu; Zhang, Xueying; Wang, Siwei (Frontiers in Psychology, 2022)
Drawing on self-determination theory, this study examines the relationship between workplace ostracism and deviant behavior by focusing on the mediating role of basic psychological needs and the moderating role of perceived inclusive climate Findings based on the analysis of 247 valid survey samples suggest that (1) workplace ostracism has a significant positive impact on employees’ deviant behavior; (2) basic psychological needs mediate the relationship between workplace ostracism and employees’ deviant behavior; and (3) employees’ perceived inclusive climate weakens the negative effect of workplace ostracism on basic psychological needs. This study develops new perspectives for workplace ostracism research, extends the factors that influence employees’ deviant behavior, and expands the boundary conditions of organizational difference in self-determination theory. Moreover, these empirical results provide important theoretical guidance to decrease employees’ deviant behavior in organizations.